Diagnostic and Treatment Reproducibility of Cervical Intraepithelial Neoplasia / Squamous Intraepithelial Lesion and Factors Affecting the Diagnosis - (:unkn) unknown (DE GRUYTER OPEN LTD, 2017)
Objective: Inter-observer differences in the diagnosis of HPV related cervical lesions are problematic and response of gynecologists to these diagnostic entities is non-standardized. This study evaluated the diagnostic reproducibility of cervical intraepithelial neoplasia (CIN) and squamous intraepithelial lesion (SIL) diagnoses. Material and Method: 19 pathologists evaluated 66 cases once using H&E slides and once with immunohistochemical studies (p16, Ki-67 and Pro-ExC). Management response to diagnoses was evaluated amongst 12 gynecologists. Pathologists and gynecologists were also given a questionnaire about how additional information like smear results and age modify diagnosis and management. Results: We show moderate interobserver diagnostic reproducibility amongst pathologists. The overall kappa value was 0.50 and 0.59 using the CIN and SIL classifications respectively. Impact of immunohistochemical evaluation on interpretation of cases differed and there was lack of statistically significant improvement of interobserver diagnostic reproducibility with the addition of immunohistochemistry. We saw that choice of treatment methods amongst gynecologists varied and overall concordance was only fair to moderate. The CIN2 diagnostic category was seen to have the lowest percentage agreement amongst both pathologists and gynecologists. We showed that pathologists had diagnostic styles and gynecologists had management styles. Conclusion: In summary each pathologist had different diagnostic tendencies which were affected not only by histopathology and marker studies, but also by the patient management tendencies of the gynecologist that the pathologist worked with. The two-tiered modified Bethesda system improved diagnostic agreement. We concluded that immunohistochemistry should be used only to resolve problems in select cases and not for every case.
Keywords: Interobserver reproducibility; SIL; CIN; Diagnosis; Gynecologist; P16(INK4A) IMMUNOHISTOCHEMISTRY IMPROVES; CANCER SCREENING-TESTS; BIOPSY SPECIMENS; INTEROBSERVER AGREEMENT; HISTOLOGICAL DIAGNOSIS; PATHOLOGISTS; VARIABILITY; P16; EXPRESSION; DYSPLASIA